Gallbladder cancer masquerading as xanthogranulomatous cholecystitis: a case report and literature review - Deng, Xu; Yang, Chun-yuan; Tian, Wei; Zhu, Zong-long; Tian, Jian-xing; Huang, Rui; Xia, Ming; Pan, Wei (Frontiers in Oncology, 2024)
Xanthogranulomatous cholecystitis (XGC) is a rare type of cholecystitis that, despite being benign poses diagnostic challenges due to its low prevalence and need for consensus on diagnostic criteria. Consequently, distinguishing XGC from gallbladder cancer (GBC) is challenging, leading to clinical misdiagnoses. This article presents a case where a patient initially diagnosed with GBC was later found to have XGC.